COMMUNITY SERVICE OF AGRO TOURISM IN SIBETAN VILLAGE - krisna, adi (International Journal of Community Service Learning, 2019)
The development of tourism in Indonesia in line with the government’s program to promote tourism as an effort to increase foreign exchange outside the oil and fuel sector. One potential alternative which could be developed in the village was agro tourism, which has been started to be developed and many of them were already successfully managed. Rilla, et al (1999) stated that the agro tourism development should be an opportunity for local farmers to increase their income for their family. Two groups that became the partners in this community service were Abian Salak agro tourism farmer group and Kebun Salak agro tourism farmer group in Sibetan village. They were selected as the partner in the activities of this program because they had same problems, namely they had low knowledge in managing their agro tourism and low knowledge in promoting their agro tourism to the public especially for domestic or international travelers who have interest in agro tourism. The solutions that were done by the team to overcome these problems were providing the training of agro tourism management that was attractive and sustainable, assisting the farmer in providing essential facilities to support activities that was offered by agro-tourism as well as their knowledge to take care those facilities, and training the farmer in promoting their agro tourism by using offline media (brochures and joining some activities of tourism festival) and online media (agro-tourism website and the use of social media). The methods that were used in these activities were assisting and training the farmer in managing their agro tourism and promoting them to the costumers. Those problems could be solved and could give a positive impact to the agro tourism management that was attractive and sustainable.